Post-Pandemic Economic System Changes - Nurma Tambunan; Rizkia Tiara Putri Gumilar; Laila Nurul Karimah (International Journal Labs, 2023)
The pandemic is a lesson for all people in various parts of the world. This can be a stepping stone for human development, it can also bring down some parties who are not ready to live it. The purpose of this paper is to describe the changes in the economic system in Indonesia after the Covid-19 pandemic. The method used is descriptive qualitative research with secondary data sources and documentation data collection methods. Based on an analysis of data obtained from journals, books, and the internet in the form of company records or documentation, government documentation or government publications, and industry analysis by the media, websites, and others, it was found that e-commerce has an important role for the Indonesian economy both in terms of actors businesses, consumers and governments.